Phase Structure, Compatibility, and Toughness of PLA/PCL Blends: A Review - Fortelny, Ivan; Ujcic, Aleksandra; Fambri, Luca; Slouf, Miroslav (Frontiers in Materials, 2019)
Results of the studies dealing with the toughness of polylactic acid/polycaprolactone (PLA/PCL) blends are analyzed with respect to the PCL particle size, PLA matrix crystallinity, and presence of a compatibilizer. It is shown that a high toughness or even »super-toughness« of PLA/PCL blends without a compatibilizer can be achieved for blends with the proper size of PCL particles. Nevertheless, the window for obtaining the super-tough PLA/PCL blends is quite narrow, as the final impact strength is very sensitive to multiple parameters: namely the blend composition, PLA matrix crystallinity, and PCL particle size. Available literature data suggest that the optimal composition for PLA/PCL blends is around 80/20 (w/w). The PLA/PCL(80/20) blends keep high stiffness of PLA matrix and the concentration of PCL particles is sufficient to achieve high toughness. The PLA/PCL(80/20) blends with low-crystallinity PLA matrix (below ca 10 %) exhibit the highest toughness for bigger PCL particles (weight average diameter above 1 μm), while the blends with high-crystallinity PLA matrix (above ca 30 %) exhibit the highest toughness for smaller PCL particles (weight average diameter below 0.5 μm). The addition of a compatibilizer may improve the toughness only on condition that it helps to achieve a suitable particle size. The toughness of both non-compatibilized and compatibilized PLA/PCL blends with optimized morphology can be more than 15 times higher in comparison with neat PLA.